APPLICATION OF VALUE FOR MONEY IN ASSESSING PERFORMANCE IN PUBLIC SECTOR HOSPITALS: A SYSTEMATIC LITERATURE REVIEW - Lombi, Fauziah Devitasari; Haliah, Haliah; Nirwana , Nirwana; Fahdal Imran Oemar , Muh Alief (Universitas Ichsan Sidenreng Rappang, 2022)
This study aims to critically discuss the application of value for money in assessing performance in public sector hospitals. The public sector hospital is a hospital that serves the community by using the maximum possible service, and of course, the public sector hospital does not pursue profit. Performance appraisal is carried out using a value-for-money application to assess how economical, efficient and effective the performance of the public sector hospital is. The research method used in this study is a Systematic Literature Review that examines the application of value for money in assessing the performance of public sector hospitals. The data analysis in this study collected several keywords and took ten selected journal articles from the last five years. This study implies the application of value for money in assessing the performance of public sector hospitals by measuring the economy, effectiveness, and efficiency. This study's findings can guide public sector hospitals to apply the value for money in assessing the performance of public sector organizations, including public sector hospitals.